Analisis Program Unggulan, Strategi Penerapan Model Pembelajaran Kontekstual dan Experiental Learning dalam Membangun Karakter Tanggung Jawab Siswa Di SDIT Alam Nurul Islam Yogyakarta - Nazula Miftahul Janah; Andira Pratama; Calista Putri Damayanti; Lewi Widiarto; Sefi Nur Maulida; Pandega Khisna Rahadi; Anggita Camelia Wibowo; Nuur Annisaa Suprihati; Taufik Muhtarom (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2026)
The formation of the character of responsibility in elementary school students is very important in the midst of various behaviors of low awareness of responsibility that arise in the school-age generation. This study aims to describe: 1) What are the leading programs at Sdit Alam Nurul Islam Yogyakarta in building the character of responsibility ; 2) how the strategy of implementing contextual learning models can build the character of responsibility of students at SDIT Alam Nurul Islam Yogyakarta; 3) how the strategy of applying the experiential learning model can build the character of Student Responsibility at Sdit Alam Nurul Islam Yogyakarta. This study uses descriptive qualitative approach with Miles and Huberman model data analysis techniques that include data reduction, data presentation, and conclusions. Validity of the data is maintained through triangulation method by comparing the results of observations, interviews, and documentation. Then analyzed descriptively based on data obtained related problems studied in the field. The results showed that there are several excellent programs in SDIT Alam Nurul Islam Yogyakarta, such as zero waste, gardening, breeding, and cooking classes. Strategies for implementing contextual learning models through a variety of real activities (learning by doing) and habituation such as caring for plants and farm animals. Meanwhile, the strategy of applying the experiential learning learning model through direct experience, reflection, and repeated application in every gardening, breeding, and cooking class.